We'll re-write the sum:Sum k(k + 3), k is an integer
number whose values are from 1 to n.
We'll remove the
brackets:
Sum k(k+3) = Sum (k^2 +
3k)
Sum (k^2 + 3k) = Sum k^2 + Sum
3k
Sum k^2 = 1^2 + 2^2 + ... + n^2 = n(n+1)(2n+1)/6
(1)
Sum 3k = 3*Sum k
Sum k = 1
+ 2 + 3 + .... + n
The sum of the first n natural terms
is:
Sum k = n(n+1)/2
3*Sum k =
3n(n+1)/2 (2)
Sum k(k+3) = (1) +
(2)
Sum k(k+3) = n(n+1)(2n+1)/6 +
3n(n+1)/2
We'll factorize by
n(n+1)/2:
Sum k(k+3) = [n(n+1)/2]*[(2n+1)/3 +
3]
Sum k(k+3) = [n(n+1)/2]*[(2n + 1 +
9)/3]
Sum k(k+3) = [n(n+1)/2]*[(2n +
10)/3]
Sum k(k+3) = 2*[n(n+1)/2]*[(n +
5)/3]
We'll simplify and we'll
get:
Sum k(k+3) = [n(n+1)(n +
5)/3]
So, the value of the general term of
the string is:
an = n(n+1)(n
+ 5)/3
No comments:
Post a Comment